Analysis of the Role of Midwives in Increasing Infant Immunization Coverage in Rural Areas - Emilia, Keva (International Journal of Nursing and Midwifery Research, 2024)
This research investigates the role of midwives in enhancing infant immunization coverage in rural areas, emphasizing their contributions to public health. Utilizing a mixed-methods approach, the study combines quantitative surveys and qualitative interviews to assess midwives' impact on vaccination rates. The findings reveal that communities with active midwifery programs achieve significantly higher immunization coverage (85%) compared to those without (65%). Statistical analyses indicate that midwife involvement increases the likelihood of complete vaccination among infants by 2.5 times. Qualitative insights highlight midwives’ roles as trusted community figures, educators, and advocates, fostering positive attitudes toward immunization. Despite these successes, the study identifies systemic barriers, including limited access to vaccines and inadequate training, which hinder midwives’ effectiveness. The research underscores the necessity for supportive policies and systemic changes to empower midwives fully. By recognizing and strengthening the role of midwives, stakeholders can improve immunization efforts and health outcomes for underserved populations.